1977
DOI: 10.1149/1.2133173
|View full text |Cite
|
Sign up to set email alerts
|

Localized Corrosion of Aluminum: Blister Formation as a Precursor of Pitting

Abstract: Blisters have been observed in the oxide film of aluminum in aqueous chloride solutions. They can be initiated by short duration (⪝ 1 msec), low voltage pulses. Such blisters grow only if the steady‐state potential of the specimen is above the pitting potential. The growth proceeds laterally along the oxide‐metal interface. Upon breaking, as a result of gas pressure from within, pitting corrosion begins. Thus, in this instance, blisters are experimentally demonstrable precursors of pits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
35
0
1

Year Published

1978
1978
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 5 publications
7
35
0
1
Order By: Relevance
“…As was mentioned above, the formation of molecular H 2 is a plausible explanation occurring during the passive state of Ta 2 O 5 and Nb 2 O 5 films. Also, it can be suggested that this phenomenon could be responsible of the breakdown of passive films as has been reported in the literature [1,2]. In the present work, we are able to predict the blistering damage of the oxide films favored in solutions with high pH.…”
Section: Kinetic Parameters Describing the Electrochemical Behavior Osupporting
confidence: 75%
See 2 more Smart Citations
“…As was mentioned above, the formation of molecular H 2 is a plausible explanation occurring during the passive state of Ta 2 O 5 and Nb 2 O 5 films. Also, it can be suggested that this phenomenon could be responsible of the breakdown of passive films as has been reported in the literature [1,2]. In the present work, we are able to predict the blistering damage of the oxide films favored in solutions with high pH.…”
Section: Kinetic Parameters Describing the Electrochemical Behavior Osupporting
confidence: 75%
“…The breakdown of oxide films may be promoted by the formation of molecular hydrogen at the metal-film interface, when a critical condition of pressure is reached. Experimental evidence for this phenomenon has been reported in the literature for different electrochemical interfaces [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Surface bubbles are pressurized by the hydrogen gas and extra material for the surface bubble wall is provided by the low-density porous hydrous oxide. The compact barrier layer cannot be penetrated by the gas molecules and hence, a high pressure of gas can develop within the surface bubbles (blisters) [21,22]. Determination of hydrogen fugacities in environmental cells by TEM was carried out by Bond et al [23].…”
Section: Resultsmentioning
confidence: 99%
“…Blister formation and rupture was first reported on Al by Bargeron and Givens 120,121 and subsequently by others. 122,123 Pit caps were observed for Al earlier.…”
Section: Oxide Blister Formation and Rupturementioning
confidence: 91%